Zn Ferti-fortification of Wheat (Triticum Aestivum L.) Using Zinc Enriched Compost and Biochar in Rainfed Area. Issue 18 (11th October 2021) - Abbas, Muhammad Subtain; Akmal, Muhammad; Khan, Khalid Saifullah; Aziz, Irfan; Rafa, Hafeez Ullah
ABSTRACT: Zinc deficiency is a global nutritional problem which is caused by low dietary intake. Wheat is mostly low in bioavailable Zn and is sensitive to zinc deficiency compared with other grain crops and as a result is reflected as cereal with low Zn efficiency. Zn deficiency prevails in arid to semiarid regions of the world for reasons of less solubility and more fixation of Zn in these soil conditions. Biofortification is currently one of the useful approaches to overcome worldwide malnourishment. A pot and two years field trials were conducted on wheat crop with following treatments: control, Zn @ 3 mg kg −1, Zn @ 6 mg kg −1, Zn @ 9 mg kg −1, Compost @ 20 t ha −1, Zn-enriched compost @ 3 mg kg −1, Zn-enriched compost @ 6 mg kg −1, Zn-enriched compost @ 9 mg kg −1, Biochar @ 20 t ha −1, Zn-enriched biochar @ 3 mg kg −1, Zn-enriched biochar @ 6 mg kg −1 and Zn-enriched biochar @ 9 mg kg −1 and treatments for field trial: control, Zn @ 18 kg ha −1, Compost @ 20 t ha −1, Zn-enriched compost @ 18 kg ha −1, Biochar @ 20 t ha −1 and Zn-enriched biochar @ 18 kg ha −1 . Results of field trial revealed that maximum grain Zn (29.18 mg kg −1 ) recorded in Zn-enriched compost @ 9 mg kg −1 and minimum (17.8 mg kg −1 ) was in control. It is concluded that Zn-enriched organic amendments especially compost found to be appropriate for yield of wheat crop and grain Zn biofortification of wheat that in result increased protein contents and reduced phytic acid concentration.